Synthesis And Application Of Molecularly Imprinted Solidphase Extraction For The Determination Of Terbutaline In Biological Matrices - Lim, Lay Lee (2006)
A study was performed to evaluate the feasibility of applying MIPs as sorbent material in SPE for clean up of terbutaline from urine and plasma samples. The imprinted polymer was prepared by using methacrylic acid (MAA) as functional monomer, ethylene glycol dimethacrylate (EGDMA) as cross-linker and salbutamol, a closely structural analogue to the targeted analyte as template molecule. Porogen used was a mixture of acetonitrile-methanol (75: 25 % v/v). Free radical polymerisation was conducted at 50 °C for 24 hours. Molar ratio of template molecule: functional monomer: cross-linker applied was fixed at 1: 4: 20. The output was a monolith macroporous polymer which required grinding and sieving to obtain fine particles between 40 to 75 pm. Soxhlet extraction method was conducted to remove the imprint molecule in order produced simultaneously using the same procedure except in the absent of template molecule. A binding study of terbutaline in several solvents was performed to determine suitable solvent for loading, selective washing and elution steps. Selectivity test on the MIP against blank polymer demonstrated that both polymers exhibited different between both polymers were observed, indicating the presence of specific binding in imprinted polymer. In blank polymer, only weak non-specific interactions occurred. Cross-specificity studies showed the MIP also exhibited molecular recognition properties towards other structurally related compounds. Spiked urine and plasma samples were diluted in 100 mM ammonium acetate buffer pH 7 (ratio = 1:1 v/v) prior to direct loading (5 mL) into a cartridge filled with 50 mg of MIP. Thereafter, the column recognition properties towards terbutaline. Significant differences in elution curves to create the recognition sites. A blank/non-imprinted polymer was